Ruthenium Chloride Catalyzed One-Pot Synthesis of Aldehydes Directly from Benzylic or Primary Alkyl Halides in Aqueous Medium - Kiran, Kiran; Muthaiah, Senthilkumar (Synlett, 2024)
We report the first example of an acid- and oxidant-free one-pot conversion of benzylic or primary alkyl halides into aldehydes by using simple ruthenium chloride as the catalyst. The developed synthetic strategy is pot-economical and is also cheap as it uses hexamethylenetetramine as a reagent, employs as little as 0.5 mol% of ruthenium chloride, and efficiently converts the benzylic or primary alkyl halides into aldehydes in aqueous medium. The methodology was also found to be highly selective, as it forms the aldehyde product exclusively without forming possible byproducts, namely amines or carboxylic acids. The methodology is also superior in comparison with the conventional Sommelet and Kornblum oxidation reactions as it avoids the use of excess acid or DMSO, and uses very cheap and ecofriendly hexamethylenetetramine as both the formylating agent and base. The recyclability of the developed catalyst system was also tested, and showed excellent activities for up to three cycles.
Keywords: ruthenium catalysis; alkyl halides; aryl halides; aldehydes; oxidation